The Effects of Digital Media Instruction on Senior High School Students’ Performance in Organic Chemistry Nomenclature - Ghartey, William; Kumi, Nelson Adjei; Bunbun, David Uwumborlame; Fenuku, Samson Dodzi; Ghartey, Kwaku Bondzie (Universitas Pendidikan Indonesia (UPI), 2024)
The objectives of the study were to determine the effect of digital media instruction on students’ academic performance in expressing organic chemistry nomenclature and to assess its effect on the male and female experimental groups of students’ performance in expressing organic chemistry nomenclature. The study adopted the non-equivalent quasi-experimental research design using the pre-test and post-test design. The sample consisted of 103 students, with 48 from Potsin Senior High School forming the control group, and 55 from Winneba Senior High School forming the experimental group, including 31 males and 24 females. A pre-test was administered to all the participants to determine their academic performance. During the study, the experimental group (Winnesec) received treatment through digital media, while the control group (Postin) was taught using traditional teaching methods. These teaching approaches were implemented over four weeks. After the treatment, a post-test was administered to both groups. The tests (pre-test and post-test) were analyzed using Microsoft Excel 2019. The results revealed that digital media was found to be more effective than the traditional method of teaching. Furthermore, results revealed that there was no differential effect of digital media on male and female students’ performance in organic chemistry nomenclature.